F40. ASSOCIATIONS BETWEEN BRAIN MORPHOLOGY AND COGNITION IN INDIVIDUALS WITH SCHIZOPHRENIA AND BIPOLAR DISORDER: A REVIEW. (9th April 2019) - Karantonis, James; Rossell, Susan; Hughes, Matthew; Wannan, Cassandra; Pantelis, Christos; Cropley, Vanessa; Rheenen, Tamsyn Van
Abstract: Background: Although nosologically distinct, there is overlap in the disease presentation of individuals with schizophrenia (Sz) and bipolar disorder (BD). Both disorders are characterized by abnormalities in cognitive performance, and in brain volume, cortical thickness and surface area. It is possible that these abnormalities are related, however the nature of the brain structure-cognition relationship in these disorders is inconclusive. This review aims to elucidate the association between measures of brain morphology and cognitive impairment in Sz and BD. Methods: Science Direct, PubMed, NCBI, and Web of Science databases were searched for papers investigating cognition and brain morphology in Sz and BD. Results: Studies indicate that grey matter volume is generally positively associated with cognitive performance. Evidence suggests common positive relationships between premorbid IQ and volume of the frontal lobe, current IQ and the temporal lobe, and verbal memory/learning and hippocampal and amygdala volume. Positive thickness-cognition relationships included non-specific executive functioning and the frontal region, attention and the temporal region, and verbal learning and memory and the temporal region, specifically the right superior gyrus. Only a handful of studies have investigated surface area with regards to cognitive impairment in Sz and BD and observed positive relationships between premorbid IQ and the frontal region, and current IQ and the temporal region. Discussion: Limitations of the literature stem from methodological and sampling issues, and from the disproportionate number of schizophrenia to bipolar disorder studies. There is a need for more novel approaches to uncover the nature of brain morphology-cognition relationships in BD and Sz.